2005
DOI: 10.1159/000089288
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Promoter Methylation of the p16 Gene on Phosphorylation of Retinoblastoma Gene Product and Growth of Hepatocellular Carcinoma Cells

Abstract: The biological significance of hypermethylation of p16 gene promoter in human hepatocellular carcinoma (HCC) cells remains to resolved. In order to clarify the significance of methylation of p16 gene promoter, we examined the methylation status of p16 gene in association with phosphorylation of retinoblastoma gene product (pRb) and cell growth in human HCC cell lines. The presence of methylation was examined by methylation-specific PCR. Expression and phosphorylation of p16 and pRb were examined by Western blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(35 reference statements)
0
8
0
Order By: Relevance
“…136 Along similar lines, histone deacetylase inhibitors can affect the DDR by modifying the expression of proteins involved in HR. 137 Indeed, the histone deacetylase inhibitor suberoylanilide hydroxamic acid efficiently inhibits the growth of hepatocellular carcinoma cells when associated with olaparib. 138 These findings are encouraging, but need further confirmation.…”
Section: Box 2 Brcanessmentioning
confidence: 99%
“…136 Along similar lines, histone deacetylase inhibitors can affect the DDR by modifying the expression of proteins involved in HR. 137 Indeed, the histone deacetylase inhibitor suberoylanilide hydroxamic acid efficiently inhibits the growth of hepatocellular carcinoma cells when associated with olaparib. 138 These findings are encouraging, but need further confirmation.…”
Section: Box 2 Brcanessmentioning
confidence: 99%
“…However, the frequency of methylation for many classically known tumor suppressors varies widely, some being as low as 15% (55–58). Using p16 as an example, analysis of the tumor samples with matched normals did not uncover tumor suppresors such as p16 and since we demonstrate the ability to detect p16 methylation in the cell line HuH7 (43) with known methylation it is likely that none of the tumors had methylation of p16 . Therefore, although improvements are always possible, we feel that our technical and analytical methods are sound.…”
Section: Discussionmentioning
confidence: 72%
“…Any ratio difference above this level was found to be methylated in one of the samples. To determine if our method could accurately identify known tumor suppressor CpG island methylation, we then analyzed the hepatocellular cancer cell line HuH7 with known methylation of the p16 promoter (43). In Figure 2F we show the detection of methylation of the region of the p16 gene CpG island commonly methylated and correlated with decreased gene transcription.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Maeta et al . observed that when HCC cells were treated with demethylating agents, there was increased expression of p16 INK4a and subsequent cell growth inhibition, suggesting that modulation of the epigenetic control of these genes may be an important target in HCC therapeutics 28 . Lee et al .…”
Section: Tumour Type‐specific Methylationmentioning
confidence: 99%